UNLOCKING THE THERAPEUTIC POTENTIAL OF MORINGA OLEIFERA LEAVES: EVALUATING THE IMPACT OF ITS NUTRITIONAL PROPERTIES - T. Talabi, Olaoluwa; O Adetona, Oloruntunmike; Oluwasanmi , Adeyemi; Godswill , Anyasor; Moyinoluwa Talabi, Joseph; Gisanrin, Olusola (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The research investigated the composition of Moringa oleifera leaves in terms of their nutritional and phytochemical properties, while also exploring the impact of solvent selection on the extraction of phenolic compounds. The study involved analyzing the leaves for essential nutrients like proteins, carbohydrates, fiber, and fats, as well as screening for various compounds such as phenols, flavonoids, alkaloids, saponins, and tannins. Phenolic compounds were extracted using methanol and hexane solvents, and the resulting extracts were examined for phlorotannins, flavonoids, and phenols. Additionally, the study evaluated the plant’s ability to scavenge DPPH and ferric (Fe3+) ion radicals, inhibit bovine serum albumin denaturation, and stabilize the human red blood cell membrane (IC50). The findings revealed that Moringa oleifera leaves are abundant in essential nutrients, phenols, and flavonoids, and moderately rich in alkaloids, saponins, and tannins, while lacking phlorotannins. The methanol extracts demonstrated higher concentrations of phlorotannins, flavonoids, and phenols compared to the hexane extract, indicating its potential for the development of novel therapeutic applications. The choice of solvent had a significant impact on the types and concentrations of phenolic compounds extracted from the plant material. Furthermore, the plant exhibited notable scavenging activity against DPPH and ferric (Fe3+) ion radicals. The methanol extract displayed stronger antioxidant and anti-inflammatory potential than the hexane extract, suggesting that Moringa oleifera leaves could serve as a natural source of bioactive compounds and antioxidants in the food and pharmaceutical industries. Overall, the study emphasizes the health benefits associated with Moringa oleifera leaves and underscores the importance of solvent selection when extracting phenolic compounds for therapeutic purposes.